Forecasting Bitcoin returns: Econometric time series analysis vs. machine learning - Theo Berger; Jana Koubová (Journal of Forecasting, 2024)
We study the statistical properties of the Bitcoin return series and provide a thorough forecasting exercise. Also, we calibrate state-of-the-art machine learning techniques and compare the results with econometric time series models. The empirical assessment provides evidence that the application of machine learning techniques outperforms econometric benchmarks in terms of forecasting precision for both in- and out-of-sample forecasts. We find that both deep learning architectures as well as complex layers, such as LSTM, do not increase the precision of daily forecasts. Specifically, a simple recurrent neural network describes a sensible choice for forecasting daily return series.
Keywords: 519; forecasting; machine learning; risk measurement; time series analysis